The Heart Dwells in Emptiness: On the Relationship between the Deep Heart of Zacharias and Hongzhi’s Empty Field - Doner, Jonathan (The international journal of religion and spirituality in society, 2017)
The concept of the heart has played a central role in the Christian tradition since ancient times. Over the course of history, it has been given a range of interpretations. The concept has received attention particularly within the Orthodox tradition, especially with respect to the practice of the Jesus Prayer, or Prayer of the Heart. Similarly, the concept of the mind has played a fundamental role in the development of Buddhist thought, particularly within the Chan/Zen tradition. This article examines these two concepts, focusing on Orthodox writer Archimandrite Zacharias’ development of the notion of the deep heart and Chinese Chan master Hongzhi’s use of the empty field. It is argued that, when viewed from a phenomenological perspective, a profound relationship exists between these ideas, supporting the presence of a fundamental psychological symmetry between the practices of these two spiritual traditions.